The Economics of the Audiovisual Industry: Financing TV, Film and Web - La Torre, Mario; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book is open access under a CC BY licence. Recent reductions in public funding for audiovisual products have led to dramatic changes in the industry. The lack of interaction between the industry and capital markets has made sourcing funds for audiovisual products especially difficult. This book explains why the distance between the audiovisual and financial markets exists, and considers the perspective of both audiovisual companies and financial intermediaries. Providing a thorough overview of the audiovisual industry in three major categories (television, cinema and web), it analyses the financing behind each. The author adapts the traditional assessment methods to include exploitation rights, distribution deals and risk determinants ; he also proposes a pricing model for the audiovisual products demonstrating that prices and values in a industry of prototype goods do not depend solely on cost and revenue. The book also includes a methodology for analysing the economics of the sector, the different sales agreements between broadcasters and the distribution deals between distributors and independent producers. Finally, a description of the main financial products for private finance is provided, as well as an explanation of how public funds can act as leverage to catalyze private resources through the use of guarantee funds. In The Economics of the Audiovisual Industry the author suggests that rather than relying on subsidized public support, the audiovisual industry should foster private-public partnerships and market dynamics to promote an alternative funding model based on a profitable and long-lasting connection between the audiovisual and financial markets. The valuation model, both for products and firms, proposed in this book are at the basis of this new approach.
Keywords: Arts; Economics; Finance, Public; Finance; Industries; Arts; Economics; Public Finance; Financial Economics; Industries